Biodiversity and climate change: ethics and science1. Issue 211 (March 2013) - Crowley, John
Abstract: Biodiversity and climate change are phenomena constructed on the basis of scientific knowledge. It is this distinctive epistemological status that gives rise to some of their most significant ethical properties. They are not autonomous scientific problems on which ethical thinking can be superimposed from the outside, any more than they are ethical concerns that have been gradually fuelled by factual elements. Rather, they are inseparably cognitive and ethical issues, in which the need for knowledge in the face of diffuse ethical concerns has always been central. After considering in more detail the attendant ethical issues, the article concludes that it is important to think about the conditions that can ensure, consistently with the commitments already made by the international community, that autonomous, integrated and rigorous science will contribute to the wellbeing of all of humanity, while preserving the integrity of the climate system and the intrinsic value of ecosystems. This is a considerable challenge, which requires a clarification of existing ethical principles, better understanding of a number of characteristics of climate change and biodiversity and, lastly, connections – some of which may be innovative – between scientific ethics, the sociology of science and the analysis of scientific policies.